The Role of PP2A in VE-cadherin Modulation in Human Cerebral Microvasculalrndothelial Cells - Alenazi, Fawza Mashouf (Trinity College Dublin. School of Medicine. Discipline of Pharmacology & Therapeutics, 2026)
Introduction: The blood–brain barrier (BBB) is a highly specialised and dynamic interface that protects the central nervous system (CNS) by tightly regulating the passage of molecules between the circulation and neural tissue. This barrier is primarily maintained by brain microvascular endothelial cells interconnected through tight and adherens junctions. Among the components of adherens junctions, vascular endothelial (VE)-cadherin plays a pivotal role in maintaining endothelial cell–cell adhesion, vascular stability, and BBB integrity. Disruption or internalisation of VE-cadherin has been implicated in numerous neurological and systemic disorders, including stroke, inflammation, and Alzheimer’s disease. The function and stability of VE-cadherin at the plasma membrane are critically influenced by its phosphorylation status. Protein phosphatase 2A (PP2A), a major serine/threonine phosphatase, is recognised as a regulator of junctional protein dephosphorylation and endothelial barrier function. Notably, PP2A has been identified as part of the VE-cadherin interactome, and previous studies suggest that it contributes to the formation of epithelial tight junctions and the maintenance of barrier integrity. However, the specific role of PP2A in regulating adherens junction components, particularly VE-cadherin, at the BBB remains unclear. Aims: This thesis aimed to investigate the role of PP2A in regulating VE-cadherin abundance and the functional integrity of the BBB using in vitro models of human brain microvascular endothelial cells. Specifically, the objectives were to (1) determine how PP2A inhibition affects VE- cadherin abundance and BBB integrity, (2) determine the broader proteomic changes associated with PP2A inhibition, and (3) determine whether metformin, a PP2A activator, can counteract these effects. Methods: Human brain endothelial cells (hCMEC/D3) were treated with the PP2A inhibitor okadaic acid (OA). VE-cadherin protein and mRNA abundance, subcellular distribution, and junctional localisation were analysed using Western blotting, RT-PCR, subcellular fractionation, and immunofluorescence. Barrier function was assessed by transwell permeability assays. PP2A activity was quantified with a phosphatase assay, and the involvement of proteasomal or lysosomal pathways was tested using MG132 and chloroquine. Proteomic alterations following OA exposure were examined using microarray analysis and bioinformatic pathway/network tools. The roles of Rab11A and Rab5A were assessed using siRNA knockdown. The impact of metformin on PP2A activity and VE-cadherin regulation was evaluated by cytotoxicity testing, PP2A activity measurement, and time-course analysis of VE-cadherin abundance. Results: OA produced a concentration-dependent reduction in VE-cadherin protein (50-70%), accompanied by its loss from endothelial junctions and a marked increase in paracellular permeability. These effects occurred without cytotoxicity and coincided with a ~60% decrease in PP2A activity. VE-cadherin reduction was prevented by proteasomal inhibition and associated with increased ubiquitination, indicating that OA promotes proteasomal degradation of VE-cadherin. Proteomic profiling identified 104 proteins altered by OA, highlighting pathways related to ubiquitination, membrane trafficking, tight junction regulation, and neurodegeneration. Rab11A upregulation was detected; however, Rab11A and Rab5A knockdown did not prevent OA-induced VE-cadherin loss. Metformin did not restore PP2A activity or reverse VE-cadherin reduction at 24 hours, although early time-course data suggested a partial transient attenuation of OA's effect at 10 hours. Conclusions: PP2A plays a critical role in maintaining VE-cadherin stability and BBB integrity. Inhibition of PP2A disrupts endothelial junctions by promoting proteasomal degradation of VE-cadherin, leading to increased barrier permeability. These findings reveal a mechanism through which PP2A dysfunction contributes to BBB impairment. Although metformin showed limited restorative capacity, early temporal effects suggest that modulating PP2A signalling may offer therapeutic potential for preserving BBB integrity under pathological conditions.
APPROVED
Keywords: VE-cadherin; Protein Phosphatase 2A; Okadaic Acid; Rab11a; Rab5a; Blood Brain Barrier; VE-cadherin internalization; VE-cadherin recycling; Metformin